Influence of organic additives on catalysts of liquid-phase cyclohexane oxidation - Mudryy, Sergiy; Reutskyy, Viktor; Ivashchuk, Oleksandr; Suprun, Oleksandr; Ivasiv, Volodymyr (Publishing House of Lviv Polytechnic National University, 2015)
Research of oxygen and nitrogen containing organic additives to the catalyst influence on the main parameters of the process of cyclohexane oxidation have been conducted. A wide range of nitrogen and oxygen containing compounds and compounds based on polyglycols with varying molecular weight have been used as additives. The obtained results have been analyzed in view of the structural features of the studied additives and the probability of their interaction with the catalyst and intermediate products of oxidation with subsequent formation of intermediate complexes or associates. Досліджено вплив кисне- та азотовмісних органічних додатків до каталізатора на склад та співвідношення продуктів окиснення циклогексану. Як додатки використовували широкий спектр азотовмісних та кисневмісних речовин з різною молекулярною масою. Одержані результати проаналізовано з огляду на особливості будови досліджуваних додатків, та ймовірності їх взаємодії з каталізатором і проміжними продуктами окиснення з подальшим утворення проміжних комплексів чи асоціатів.
Вплив органічних додатків на каталізатори процесу рідиннофазного окиснення циклогексану
Keywords: cyclohexane; oxidation; catalysis; chelates; complex compounds; циклогексан; окиснення; каталіз; хелати; комплексні сполуки